(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the position of Law-enforcement officers, the work has been considered as a very hard, dangerous and stressful job. Police officers’ decisions are frequently not supported by the organisation or the police supervisors. The decision that polices officers make will be reviewed and scrutinized in a variety of situations. Lack of support from co-workers, supervisors and department help is the most common cause of workplace stress and is also one of the worst stressors. Work place stress can lead to a variety of issues, including depression, physical and mental health issues and burnout conditions.